Activation of orexin-2 receptors in the Kӧlliker-Fuse nucleus of anesthetized mice leads to transient slowing of respiratory rate - Varga, Adrienn G.; Whitaker-Fornek, Jessica R.; Maletz, Sebastian N.; Levitt, Erica S. (Frontiers in Physiology, 2022)
Orexins are neuropeptides originating from the hypothalamus that serve broad physiological roles, including the regulation of autonomic function, sleep-wake states, arousal and breathing. Lack of orexins may lead to narcolepsy and sleep disordered breathing. Orexinergic hypothalamic neurons send fibers to Kӧlliker-Fuse (KF) neurons that directly project to the rostroventral respiratory group, and phrenic and hypoglossal motor neurons. These connections indicate a potential role of orexin-modulated KF neurons in functionally linking the control of wakefulness/arousal and respiration. In a reduced preparation of juvenile rats Orexin B microinjected into the KF led to a transient increase in respiratory rate and hypoglossal output, however Orexin B modulation of the KF in intact preparations has not been explored. Here, we performed microinjections of the Orexin B mouse peptide and the synthetic Orexin 2 receptor agonist, MDK 5220, in the KF of spontaneously breathing, isoflurane anesthetized wild type mice. Microinjection of Orexin-2 receptor agonists into the KF led to transient slowing of respiratory rate, which were more exaggerated in response to Orexin-B than MDK 5220 injections. Our data suggest that Orexin B signaling in the KF may contribute to arousal-mediated respiratory responses.